2022
DOI: 10.1167/iovs.63.9.5
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Expression of CFH Rare Variants in Age-Related Macular Degeneration Patients in the Coimbra Eye Study

Abstract: Purpose To determine the association between rare genetic variants in complement factor H ( CFH ) and phenotypic features in age-related macular degeneration (AMD) patients from the Coimbra Eye Study (CES). Methods AMD patients from the Incidence CES (NCT02748824) underwent ophthalmologic examination and color fundus photography, spectral-domain optical coherence tomography (SD-OCT), fundus autofluorescence, and near-infrared imaging. Multimod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…5,6,9 Plus, in this GWAS, a significant burden of rare variants was observed in the CFH and CFI genes, and others confirmed that rare variants conferred a high risk of disease and were associated with a more severe phenotype, including widespread extramacular drusen deposition. 5,[10][11][12][13][14] In AMD, most genotype-phenotype associations performed to date rely only on the phenotypic analysis of the macular area, with few studies considering extramacular features such as drusen and pigmentary changes. 15,16 Some, however, found that these features are frequently seen in eyes with AMD and are more prevalent with increasing drusen burden in the macula, but their relevance for the development and severity of AMD is not fully understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5,6,9 Plus, in this GWAS, a significant burden of rare variants was observed in the CFH and CFI genes, and others confirmed that rare variants conferred a high risk of disease and were associated with a more severe phenotype, including widespread extramacular drusen deposition. 5,[10][11][12][13][14] In AMD, most genotype-phenotype associations performed to date rely only on the phenotypic analysis of the macular area, with few studies considering extramacular features such as drusen and pigmentary changes. 15,16 Some, however, found that these features are frequently seen in eyes with AMD and are more prevalent with increasing drusen burden in the macula, but their relevance for the development and severity of AMD is not fully understood.…”
mentioning
confidence: 99%
“…The Coimbra Eye Study (CES) is a two-visit epidemiologic population-based study on the prevalence and incidence of AMD in a Portuguese population (NCT01298674, NCT02748824), and we have previously reported on the genetics influencing AMD risk. 14,[22][23][24][25][26] The present work aims to expand our genotype-phenotype analysis by evaluating the association between the sequenced risk variants, the GRS, and the presence of extramacular drusen in subjects with and without AMD.…”
mentioning
confidence: 99%